The Influence Of Green Human Resource Management On Corporate Performance Through Green Organizational Culture In Manufacturing Companies Cilegon - Sumarjo, Wahid; Triatmanto, Boge (Proceedings of International Conference of Graduate School on Sustainability, 2026)
Company performance is an important measure that describes the organization's ability to achieve preset goals. In the literature, company performance is often seen as a multidimensional concept that includes financial, operational, innovation, and sustainability aspects. A modern approach to corporate performance assesses not only an organization's success from economic gains, but also its contribution to the environment, society, and corporate governance. In general, financial performance is the most commonly used element to measure an organization's success, including indicators such as profitability, return on assets (ROA), and return on equity (ROE). Corporate performance measurement frameworks have evolved a lot, from traditional approaches that only assess financial performance to holistic approaches such as the Sustainability Balanced Scorecard (SBSC) that combine financial and sustainability aspects. In addition, the Environmental, Social, and Governance (ESG)-based approach is the main framework for measuring organizational sustainability, which includes not only environmental impacts but also social responsibility and governance. In recent years, the company's leaders, in this case, the Board of Directors and managers, are increasingly aware that to be able to survive in the national and global arena, the company is required to carry out environmentally friendly implementation to achieve sustainable Company Performance. This study aims to analyze the influence of Green Human Resource Management on company performance, analyzing the influence of Green Organizational culture on company performance. And Green Human Resource Management on the Company's performance through Green Organizational culture on the Company's performance. The practical contribution of this research is as a reference for the Board of Directors and stakeholders to improve sustainable corporate performance by implementing Green Human Resource Management and Green Organizational culture. This study uses a quantitative approach, the population in this study is company employees with Manager and Superintendent levels in the Cilegon Industrial area Banten with an analysis sample of 149 employees. The data analysis technique uses the Structural Equation Modelling model. The results of this research analysis show that Green Human Resource Management has a positive and significant effect on company performance, Green Organizational Culture can mediate Company Performance.